Straw Mills of Russian Sociological Expertise - Dmitry Rogozin (Journal of Economic Sociology, 2019)
The article corresponds to Nikolai Babich’s detailed remarks about the paper “Criticism of the Survey Approach for Analyzing the Mutual Similarity in the Appearance of Consumer Products Within One Product Category,” published in the Journal of Economic Sociology (2018, vol. 19, no 2, pp. 86–117). The author outlines the basic problems of the current sociological expert evaluation in Russia and proposes options for methodological work aimed at adopting experience from the established contractual procedure for the verification of scientific truth. This article presents some criticism of methods and procedures applied in the field of sociological expert evaluation which turned out to be closed and non-public in Russia. This sociological field has some notable features, including uncritical attitudes toward what and how expert evaluations are produced, uncertainty in the usage of methods, ignorance of international research experience and the non-transparency of methodology and tools. For solving the mentioned problems which the Russian sociological expertise meets, Dmitry Rogozin proposes that sociologists be more active in three directions: 1) conducting a cognitive analysis of survey toolkits embedded in court practice; 2) reconstructing experimental plans with an analysis of applied samplings; and 3) organizing institutional reviews of sociological expert evaluations.